2023
DOI: 10.1158/1078-0432.ccr-23-0212
|View full text |Cite
|
Sign up to set email alerts
|

ENIGMACHEK2gether Project: A Comprehensive Study Identifies Functionally ImpairedCHEK2Germline Missense Variants Associated with Increased Breast Cancer Risk

Abstract: Purpose: Germline pathogenic variants in CHEK2 confer moderately elevated breast cancer risk (odds ratio, OR ∼ 2.5), qualifying carriers for enhanced breast cancer screening. Besides pathogenic variants, dozens of missense CHEK2 variants of uncertain significance (VUS) have been identified, hampering the clinical utility of germline genetic testing (GGT). Experimental Design: We collected 460 CHEK2 missense VUS identified by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Such an approach is supported by the finding that concordant data from multiple assays has significantly more overlap with independent VEP predictions than data from a single assay. The value of a second, confirming assay is further supported by an analysis of ENIGMA patient data and two functional assays (KAP1 phosphorylation and CHK2 phosphorylation) carried out by Stolarova et al 22 , which shows that CHK2 variants confirmed to be damaging in more assays are associated with increasing risk for breast cancer. For example, the 140 variants that either of their functional assays classified as damaging, even if the two assays were discordant, showed a combined increased risk for breast cancer (OR 2.29; 95% CI 1.97 – 2.66), while the 91-variant subset of these that were confirmed to be damaging in our screen showed a marginally increased risk (OR 2.95; 95% CI 2.36 – 3.69), and the risk conferred by 74 variants confirmed to be damaging in all three assays was even higher (OR 3.05; 2.39 – 3.90) (Supplemental Table 3 and 22 ).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Such an approach is supported by the finding that concordant data from multiple assays has significantly more overlap with independent VEP predictions than data from a single assay. The value of a second, confirming assay is further supported by an analysis of ENIGMA patient data and two functional assays (KAP1 phosphorylation and CHK2 phosphorylation) carried out by Stolarova et al 22 , which shows that CHK2 variants confirmed to be damaging in more assays are associated with increasing risk for breast cancer. For example, the 140 variants that either of their functional assays classified as damaging, even if the two assays were discordant, showed a combined increased risk for breast cancer (OR 2.29; 95% CI 1.97 – 2.66), while the 91-variant subset of these that were confirmed to be damaging in our screen showed a marginally increased risk (OR 2.95; 95% CI 2.36 – 3.69), and the risk conferred by 74 variants confirmed to be damaging in all three assays was even higher (OR 3.05; 2.39 – 3.90) (Supplemental Table 3 and 22 ).…”
Section: Discussionmentioning
confidence: 82%
“…Another recent large study functionally characterized 427 CHEK2 VUSs selected by the international ENIGMA (Evidence-based Network for the Interpretation of Germline Mutant Alleles) consortium for variants with an association to an increased risk of breast cancer 22 . That study used two parallel functional assays that quantified the phosphorylation of the KRAB-associated protein (KAP1) at S473 and autophosphorylation of CHK2 at S516.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These assays are designed to assess the impact of a particular variant on the structure and functionality of the corresponding protein, providing an estimated VUS pathogenicity [37]. Large investigator consortia, like ENIGMA or INSIGHT, have started to form, with the aim of collecting a large amount of data on VUSs and subsequently using machine learning prediction models or functional assays in determining the significance of variants [39][40][41].…”
Section: Discussionmentioning
confidence: 99%